Investigating students’ perception of using wikis in academic writing course - Zailin Shah Yusoff,; Nik Aloesnita Nik Alwi,; Ainol Haryati Ibrahim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Wikis are emergent technologies which are increasingly used in writing classrooms. These web-based, authoring tools have been used in academic writing classrooms and specifically for collaborative work. This study investigated students’ perception of using wikis for collaborative writing. Four-hundred twenty four undergraduate students enrolled in an academic writing course participated in the survey. In the course, students wrote, revised and submitted group research reports via wikis. This paper discusses two main issues, the first is to determine group participation level during group work via wikis and the second is, to identify the preferred collaborative writing mode. Findings indicate that students did not face major problems working together online. On the one hand, the students reported that wikis were useful for data storage and group work task completion. In addition, they claimed that using wikis for group work encouraged group participation. On the other hand, the students argued for the preference for face-to-face discussion during collaborative writing.